Fibroblast Growth Factor 23 Signaling Does Not Increase Inflammation from Pseudomonas aeruginosa Infection in the Cystic Fibrosis Bronchial Epithelium - Meghan June Hirsch; Emma Lea Matthews; Seth Bollenbecker; Molly Easter; Megan R. Kiedrowski; Jarrod W. Barnes; Stefanie Krick (Medicina, 2023)
Background and Objectives: Chronic inflammation due to Pseudomonas aeruginosa (PA) infection in people with cystic fibrosis (CF) remains a concerning issue in the wake of modulator therapy initiation. Given the perpetuating cycle of colonization, infection, chronic inflammation, and recurrent injury to the lung, there are increases in the risk for mortality in the CF population. We have previously shown that fibroblast growth factor (FGF) 23 can exaggerate transforming growth factor (TGF) beta-mediated bronchial inflammation in CF. Our study aims to shed light on whether FGF23 signaling also plays a role in PA infection of the CF bronchial epithelium. Materials and Methods: CF bronchial epithelial cells were pretreated with FGF23 or inhibitors for FGF receptors (FGFR) and then infected with different PA isolates. After infection, immunoblot analyses were performed on these samples to assess the levels of phosphorylated phospholipase C gamma (PLCγ), total PLCγ, phosphorylated extracellular signal-regulated kinase (ERK), and total ERK. Additionally, the expression of FGFRs and interleukins at the transcript level (RT-qPCR), as well as production of interleukin (IL)-6 and IL-8 at the protein level (ELISA) were determined. Results: Although there were decreases in isoform-specific FGFRs with increases in interleukins at the mRNA level as well as phosphorylated PLCγ and the production of IL-8 protein with PA infection, treatment with FGF23 or FGFR blockade did not alter downstream targets such as IL-6 and IL-8. Conclusions: FGF23 signaling does not seem to modulate the PA-mediated inflammatory response of the CF bronchial epithelium.